Fourfold Faster Rate of Genome Rearrangement in Nematodes Than in Drosophila - Coghlan, Avril (Cold Spring Harbor Laboratory Press, 2002)
We compared the genome of the nematode Caenorhabditis elegans to 13% of that of Caenorhabditis briggsae, identifying 252 conserved segments along their chromosomes. We detected 517 chromosomal rearrangements, with the ratio of translocations to inversions to transpositions being ∼1:1:2. We estimate that the species diverged 50–120 million years ago, and that since then there have been 4030 rearrangements between their whole genomes. Our estimate of the rearrangement rate, 0.4–1.0 chromosomal breakages/Mb per Myr, is at least four times that of Drosophila, which was previously reported to be the fastest rate among eukaryotes. The breakpoints of translocations are strongly associated with dispersed repeats and gene family members in the C. elegans genome. [The following institution kindly provided reagents, samples or unpublished information as indicated in the paper: Genome Sequencing Center, Washington University School of Medicine, St. Louis.]